2020
DOI: 10.1161/jaha.119.015716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucagon‐Like Peptide‐1 Receptor Agonists, Sodium‐Glucose Cotransporter‐2 Inhibitors, and Their Combination on Endothelial Glycocalyx, Arterial Function, and Myocardial Work Index in Patients With Type 2 Diabetes Mellitus After 12‐Month Treatment

Abstract: Background We investigated the effects of insulin, glucagon‐like peptide‐1 receptor agonists ( GLP ‐1 RA ), sodium‐glucose cotransporter‐2 inhibitors ( SGLT ‐2i), and their combination on vascular and cardiac function of patients with type 2 diabetes mellitus. Methods and Results A total of 160 patients with type 2 diabetes mellitus were randomized to insulin (n=40), liraglutide (n=40), emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 52 publications
6
114
0
Order By: Relevance
“…Our data showed that indices of myocardial work were deteriorated in hypertensive patients comparing with normotensive controls, but these parameters were even worse in hypertensive patients with concomitant DM. This is in line with recently published studies, 19‐23 but also adds some novelties such as concomitant effect of hypertension and diabetes on myocardial work. The present findings revealed that only constructive myocardial work was higher in patients with concomitant hypertension and DM comparing with those who had only hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Our data showed that indices of myocardial work were deteriorated in hypertensive patients comparing with normotensive controls, but these parameters were even worse in hypertensive patients with concomitant DM. This is in line with recently published studies, 19‐23 but also adds some novelties such as concomitant effect of hypertension and diabetes on myocardial work. The present findings revealed that only constructive myocardial work was higher in patients with concomitant hypertension and DM comparing with those who had only hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Newer antidiabetic agents, such as sodium-glucose cotransporter-2 (SGLT-2) inhibitors [219,220] and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) [221], decreased PWV in studies in patients with type-2 diabetes. Saxagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, prevented vascular remodeling and OS in a genetic model of diabetes [221].…”
Section: Antihypertensive and Antidiabetic Agentsmentioning
confidence: 99%
“…All treatments led to reductions in HbA1c, total cholesterol, LDL cholesterol and triglycerides. The combination of empagliflozin and liraglutide was associated with the most favorable effects on myocardial functional markers (global longitudinal and radial strains, myocardial work index) and metabolic parameters (BMI, endothelial glycocalyx thickness, central systolic blood pressure) (Ikonomidis et al, 2020).…”
Section: Implications For the Choice Of The Antidiabetic Drugsmentioning
confidence: 97%
“…Treatment of obese, non-diabetic patients with exenatide and dapagliflozin for 52 weeks reduced bodyweight, total adipose tissue volume, LDL cholesterol, triglycerides, systolic blood pressure and the proportion of patients with pre-diabetes (Lundkvist et al, 2017). In a trial with T2D patients, the influence of liraglutide-empagliflozin combination therapy was compared to monotherapy with liraglutide, empagliflozin or insulin as add-on to metformin (Ikonomidis et al, 2020). All treatments led to reductions in HbA1c, total cholesterol, LDL cholesterol and triglycerides.…”
Section: Implications For the Choice Of The Antidiabetic Drugsmentioning
confidence: 99%